DETERMINAN NILAI PERUSAHAAN MANUFAKTUR DI INDONESIA - Iswara, Ulfah Setia; Setyabudi, Teguh Gunawan; Susanti (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2022)
This study aims to conduct an empirical test of the effect of leverage, profitability, and firm size on firm value. The valuation of the company's share price is based on the company's ability to generate profits. The study was conducted on manufacturing companies listed on the Indonesia Stock Exchange in the period 2018 to 2020. The sample companies were 126 companies using the purposive sampling method. The data analysis technique used multiple regression analysis. The results obtained that leverage has a significant positive effect on firm value. The use of borrowed funds to generate profits will increase the value of the company. Profitability as measured by Return on Assets has a significant effect in a positive direction on firm value. This shows that the greater the profit generated, the value of the company also increases. Another factor that has an influence on firm value is firm size. Firm size seen from the total asset value has a significant positive effect on firm value.